2010
DOI: 10.1002/jpln.200900260
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of selenite uptake by maize roots in response to different pH levels

Abstract: In selenite solutions, H 2 SeO 3 , HSeO À 3 , and SeO 2À 3 are in equilibrium in proportions that vary with solution pH. The physiological characteristics of selenite uptake were studied with excised roots of maize (Zea mays L.) seedlings at pH 3.0, 5.0, and 8.0. The results showed that 0.10 mM 2,4-dinitrophenol (DNP), 1.0 mM sodium fluoride (NaF), and a temperature of 4°C inhibited selenite uptake by maize roots by 16%, 20%, and 23% at pH 3.0, by up to 80%, 79%, and 78% at pH 5.0, and by 5%, 9%, and 16% at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 31 publications
0
33
6
1
Order By: Relevance
“…Silver interacts with the amino acid histidine in addition to cysteine (Table 1), but the reaction between silver and imidazole N of histidine is only supposed to occur at silver concentration of more than 200 M. Like mercury, use of silver nitrate in a recent citation was found to have toxic side effect on K + homeostasis and cellular integrity even in lower doses (Coskun et al, 2012). However, concentrations of silver of 10-50 M used in maize root studies showed no significant inhibition (Soós et al, 2010;Zhang et al, 2010). A silver concentration of 500 M used in this study was also used in studies of AQP in barley (Volkov et al, 2007) and in tomato (Kanai et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Silver interacts with the amino acid histidine in addition to cysteine (Table 1), but the reaction between silver and imidazole N of histidine is only supposed to occur at silver concentration of more than 200 M. Like mercury, use of silver nitrate in a recent citation was found to have toxic side effect on K + homeostasis and cellular integrity even in lower doses (Coskun et al, 2012). However, concentrations of silver of 10-50 M used in maize root studies showed no significant inhibition (Soós et al, 2010;Zhang et al, 2010). A silver concentration of 500 M used in this study was also used in studies of AQP in barley (Volkov et al, 2007) and in tomato (Kanai et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…LaCl 3 is a Ca 2+ channel blocker (Ebbs et al 2008). Na 3 VO 4 , HgCl 2 , and AgNO 3 are inhibitors of the ion transporting (Ebbs et al 2008;Zhang et al 2010). TEACl is an anion channel inhibitor (Zhang et al 2010).…”
Section: Effect Of Inhibitors On Ferro-cyanide Uptake By Detached Rootsmentioning
confidence: 99%
“…Na 3 VO 4 , HgCl 2 , and AgNO 3 are inhibitors of the ion transporting (Ebbs et al 2008;Zhang et al 2010). TEACl is an anion channel inhibitor (Zhang et al 2010). The initial pH of spiked solution was adjusted to 7.5 with 0.1% NaOH.…”
Section: Effect Of Inhibitors On Ferro-cyanide Uptake By Detached Rootsmentioning
confidence: 99%
“…channel blocker (Ebbs et al 2008). Na 3 VO 4 , HgCl 2 , and AgNO 3 are inhibitors of the ion transporting (Ebbs et al 2008;Zhang et al 2010). TEACl is an anion channel inhibitor (Zhang et al 2010).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Na 3 VO 4 , HgCl 2 , and AgNO 3 are inhibitors of the ion transporting (Ebbs et al 2008;Zhang et al 2010). TEACl is an anion channel inhibitor (Zhang et al 2010). The initial concentration of spiked solution was 10.50 (±0.225) mg CN/L.…”
Section: Plant Materialsmentioning
confidence: 99%